Kajian Eksperimental Performansi Pompa dengan Kapasitas 1,25 m3/menit Head 12 m jika Dioperasikan Sebagai Turbin - Himsar Ambarita (Jurnal Dinamis, 2011)
AbstractPump as Turbine or PAT is a promising aplication for harvesting small scale hydro power.In comparison with a turbine. pump is cheap, easy to install, and available in market withvarious sizes. Since so PAT is suitable for micro hydropower and for rural areas a typical offgridvillages in Indonesia. However, a pump is originally designed efficiently to convert powerinto fluid energy, not reverse, for converting fluid energy into power. Thus, experiments areextremely needed in order to search the best operation point of a PAT. This paper deals withexperimental study on pump operated as a turbine. A local produced pump with capacity 1.25m3/minute and head 12 m is tested in the laboratory with falling water from 5.18 m and 9.29 m.The pump is coupled with a generator and the electicity produced is used to light five lampswith 100W each.The results show that the best efficiency is 31,39% at 10,38 L/minute andhead 5,18 m. The maximum output power is 400W which is sufficient to generate electricity forsmall house. The experimental results agree well with the teoretical ones. However, the graphsplotted reveal that the present PAT is still far from its best efficiency point.This is due tolimitation of the experimental apparatus. Further modification or using smaller pumps aresuggested to explore the best efficiency point of PAT.Keywords: hydropower, PAT, renewable energy.